Reflexivity-12 to Roikhan-47 as Ontological Worship on Islam and Science in the Economic Covid Era - R. Mochamad A. (Proceeding International Conference on Religion, Science and Education, 2022)
The purpose of this study is to analyze the philosophical worship of Reflexivity-12 (R12) and Roikhan-47 (R47) with Qur’an 51.56 on Islam and science in the economic covid era. R12 is the source of creation that consists of constant 12. R47 is the reflexivity of object source in the complex structure. These research objects are R-12 and R-47 formula with Qur’an. Research is studied through reference to books, journals, holy books, and other electronic media. The methodology uses analytical descriptive. The method uses reflexivity, similarity, and analogies with a benchmark of hahslm 472319. The result is the source object as R-12 or worship appeared before R-47 as the universe in the form of source object reflexivity that has a complex structure. The Qur’an 51.56 as fundamental guidance about the existence of worship before humans created. The reflexivity of the architect that has a blueprint of the universe house then creates a universe house, becomes evidence as logical thinking empirically. The mirroring system also corresponds to a projector paradigm consisting of the notebook, projector, and screen. The mirror's position consisted of shadow, mirror, and people. The blueprint presence is the reflexivity of 12 as a constant creation source from Qur’an 51.56 verse number (1+5) times (5+6) root of digit 2 becomes 6x2=12. This R12 has reflexivity of Salat Jamak where 1 salat Subuh and 2 salat Jamak (Dzuhur Asar and Magrib Isa). R12 as religion and R47 as science is 1 object in the form of God's creation. The architect has only 1 finished universe house including 1 blueprint of the universe house. The conclusion is R12 and R47 are the same 1 object. Religion and science also are the same 1 object. Universe has only 1 God, then God only gives 1 information to humans and there is no separation between religion and science. This unification of religion and science also happened in the pandemic era with the economic crisis.